UTILAZATION POWER POINT IN LEARNING FOR CLASS VI STUDENTS OF SDN 2 KARANGLO INCREASING CHILDREN’S INTEREST IN LEARNING - Suhudi, Nur (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This research uses a development procedure which produces the final design in the form of developing Information Technology-based learning media using interactive Powerpoint. Researchers developed this product by combining research steps from Borg and Gall and the ASSURE model. The product developed in this research is Information Technology-based learning media referring to the 2013 curriculum for class VI students at Karanglo 2 State Elementary School. Based on the development procedure steps above, the researcher only limited it to 5 development procedure steps, namely (1) potential and problems, (2) data collection, (3) product design, (4) expert validation, and (5) design revision. . This is due to the limited time required for research and this information technology-based learning media was created to be used by teachers so that it was sufficiently validated by four grade VI elementary school teachers who created information technology-based learning media in implementing the 2013 Curriculum with the help of researchers.